The one pot asymmetric synthesis of 3, 3′-pyrrolidonyl spiroxindoles via a regio- and stereoselective domino reaction. Issue 35 (21st August 2019) - Hajra, Saumen; Bhosale, Suhas Shivajirao; Hazra, Atanu; Kanaujia, Nikhil
Abstract : The asymmetric synthesis of 4-aryl-3, 3′-spiropyrrolidonyl oxindoles with excellent stereoselectivity (dr >99 : 1 and an ee up to >99%) was achieved via a domino reaction. Abstract : A highly efficient regio- and stereoselective domino aziridine ring opening and lactamization reaction between aziridines and 3-carboxy oxindole esters has been developed for the one pot asymmetric synthesis of 4-aryl-3, 3′-spiropyrrolidonyl oxindoles with excellent selectivity (dr >99 : 1 and ee up to >99%). It was further extended to a sequential one pot protocol for the asymmetric synthesis of NH-free 3, 3′-pyrrolidonyl spiroxindole, maintaining the same selectivity.